An Unexpected Property of Fractional Difference Operators: Finite and Eventual Monotonicity - Lizama-Yanez, C (John Wiley and Sons Ltd, 2024)
We consider the relationship between the sign of the fractional difference (Formula presented.) and the positivity or monotonicity of (Formula presented.). Our focus is on the case in which the fractional difference can be negative, and we show that surprisingly, (Formula presented.), where (Formula presented.) is a constant, can still imply that (Formula presented.) is increasing or is positive. We also consider the setting of sequential difference operators such as (Formula presented.) for suitable choices of the parameters (Formula presented.) and (Formula presented.). As is demonstrated by explicit examples, our results substantially improve some recent results in the literature and, moreover, shed light on some previous observations that heretofore were only able to be investigated by numerical simulations. We also provide applications of our results to an analysis of fractional-order initial value problems. © 2024 John Wiley & Sons Ltd.
Keywords: convolution; discrete fractional calculus; monotonicity; negative lower bound; positivity